IV International Tourism, Hospitality & Gastronomy Congress: Conference Proceedings - Universidad San Ignacio de Loyola (2023)
Tourism is considered a social phenomenon that, when properly managed, allows country’s economic, social and environmental development. From the majesty of a natural landscape to the richness of a unique culture, tourism gives us the opportunity to explore and discover the beauty and diversity of our planet. Yet, as tourism has become a global industry, the responsibility has also arisen to research, innovate and develop projects that focus on priority trends and needs that allow the development of local communities and the sector’s growth. In this sense, the IV International Tourism, Hospitality & Gastronomy Congress, funded by the National Council of Science, Technology and Technological Innovation (CONCYTEC) through PROCIENCIA and organized by the Faculty of Hotel Administration, Tourism and Gastronomy, becomes an exchange of experiences space between academia, the public sector, the private sector and local communities. The congress was born with a prospective vision of addressing the advances and trends of the tourism, hotel and gastronomic industry, providing a space for dialogue, reflection, dissemination of knowledge and experiences linked to innovation and technology to promote the sustainability and governance of emerging and consolidated national tourist destinations. This book compiles important studies related to the use of digital tools and learning styles, crisis management in hotel companies, economic growth and entrepreneurship, municipal management, participatory strategies for sustainability and accessible tourism from an ethnographic perspective. We invite all actors involved in the tourism industry, from travelers and businessmen, to governments and non-governmental organizations, to consider the research presented as inspirations to have updated information and serve as a contribution to the development of the sector. We thank the authors who have contributed with their research, the members of the scientific committee who have collaborated with the peer review to maintain scientific rigor, we are sure that this book will allow us to delve deeper into various relevant topics that contribute to the sector. From the academy we remain committed to promoting research and contribution to global knowledge.